Ethical concepts: what does best interests actually mean?. (2nd July 2019) - Ellis, Peter
Abstract : Healthcare professionals must consider the best interests of their patients. In this article, Peter Ellis looks at how best interests are defined and how they are best served for the benefit of the kidney care patient